PENGARUH FAKTOR INTERNAL TERHADAP MANAJEMEN LABA : Studi Empiris Pada Perusahaan Transportasi dan Logistik di BEI - Septiandi, Dian Ayu; Aminah, Aminah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the influence of internal factors (Tenur CEO, independent board of commissioners and earning power) on profit management practices. The object of this research is transportation and logistics companies listed on the Indonesia Stock Exchange during the 2021-2023 period. A total of 66 samples were selected using the purposive sampling technique, which is a method of selecting samples based on certain criteria. This study adopts a quantitative approach with data analysis conducted using the 2018 version of SPSS software. The results of the study show that the CEO of Tenur has no influence on profit management. In contrast, the independent board of commissioners had a significant negative influence on profit management, and earning power was found to have a positive and significant effect on profit management.